Reduction in thermal loading of buildings by high-albedo materials - Lau, Jia Hui. (2013)
Thermal loadings from the surrounding of the building into the building interior are a major concern, directly related to the usage of cooling devices to cool the interior of the building. Ambient temperatures in Singapore are relatively higher as compared to countries in other regions due to the Urban Heat Island (UHI) effects encountered and the geographical location on the globe. UHI causes a higher temperature of several degrees Celsius in urban area as compared to its surrounding suburban and rural areas. With the higher temperature, thermal loadings into the interior of the buildings reached a level significantly to cause thermal discomfort to the occupants of the buildings. Mitigation devices such as air-conditioner systems are most commonly used to achieve thermal comfort within the buildings. However, the excessive usage of mitigation devices brings up environmental and energy consumption issues.